Laughter therapy as an intervention to promote psychological well-being of volunteer community care workers working with HIV-affected families - Irene Hatzipapas; Maretha J. Visser; Estie Janse van Rensburg (Taylor & Francis Group, 2017)
The study explores the experiences of volunteer community care workers working with HIV-affected families, participating in laughter therapy. Laughter therapy is being used as an intervention to positively influence individuals experiencing various forms of emotional distress. Community care workers play a vital role in the support of the HIV/AIDS-infected and -affected members in communities. The nature of this type of work and their limited training contributes to high levels of secondary trauma and emotional exhaustion. The purpose of the study was firstly, to explore the effects of working with orphans and vulnerable children (OVC) on the community care workers and secondly, to establish the impact that laughter therapy has to positively combat stresses of working within the care workers' environment. All the community care workers from a community-based organisation that provides care for HIV/AIDS-infected and -affected OVC and their families in the greater region of Soweto, South Africa, took part in daily laughter therapy sessions for one month. To assess the experiences of participants of laughter therapy, seven community care workers agreed to participate in a mixed method assessment. Interviews were conducted before and after the intervention using the Interpretative Phenomenological Analysis as framework. As supportive data, a stress and anxiety and depression scale were added in the interview. Participants reported more positive emotions, positive coping, improved interpersonal relationships and improvement in their care work after exposure to laughter therapy. Quantitative results on stress, anxiety and depression for each participant confirmed observed changes. Laughter therapy as a self-care technique has potential as a low-cost intervention strategy to reduce stress and counteract negative emotions among people working in highly emotional environments.